The Effect of Khat Learning and Learning Motivation on Students' Ability to Write the Quran at MTs Nurul Muhajirin Labanan Makarti - Sriyanto; Benny Prasetya; Muhammad Alfi Syahrin; Khamam Khosiin (PT. Caesarindo Triloka Persada, 2026)
This study examines the effect of khat learning and learning motivation on students’ Qur’anic writing ability at MTs Nurul Muhajirin Labanan Makarti. The study used a quantitative approach with a correlational design. A total of 51 students were selected using purposive sampling. The independent variables were khat learning and learning motivation, and the dependent variable was Qur’anic writing ability. Data were collected through a Qur’anic writing test and a learning motivation questionnaire. Multiple linear regression analysis was conducted after confirming that all statistical assumptions were met. The results showed that khat learning and learning motivation had a significant simultaneous and partial effect on students’ Qur’anic writing ability. These findings indicate that structured khat learning, supported by strong learning motivation, effectively improves students’ competence in Qur’anic writing in the Islamic junior high school setting.